2015
DOI: 10.2298/gensr1501253k
|View full text |Cite
|
Sign up to set email alerts
|

A linkage map of chickpea (Cicer arietinum L.) based on population from ILC3279×ILC588 crosses: Location of genes for time to flowering, seed size and plant height

Abstract: Quantitative traits of seed size, plant height and days to flowering were studied in a chickpea intraspecific F3:4 lines population derived from a ILC3279?ILC588 cross. The lines were genotyped with random amplified polymorphic DNA (RAPD), universal rice primer (URP) and sequence tagged microsatellite site (STMS) markers, and a genetic map composed of 7 linkage groups (LGs) covering 285.3 cM was constructed. Quantitative trait loci (QTLs) for the three characters were detected in LG2, LG3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…To ascertain the robustness and novelty of the identified PH QTLs, the major genomic regions underlying six robust PH QTLs were compared/correlated with that of previous QTL mapping studies based on correspondence of physical positions of SNPs covering (flanked/linked) the target QTL intervals3758. None of these six QTLs were found to be congruent with previous QTL mapping studies involving diverse intra- and inter-specific mapping populations of chickpea.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…To ascertain the robustness and novelty of the identified PH QTLs, the major genomic regions underlying six robust PH QTLs were compared/correlated with that of previous QTL mapping studies based on correspondence of physical positions of SNPs covering (flanked/linked) the target QTL intervals3758. None of these six QTLs were found to be congruent with previous QTL mapping studies involving diverse intra- and inter-specific mapping populations of chickpea.…”
Section: Discussionmentioning
confidence: 89%
“…Considering the added-advantages of QTL and association mapping in quantitative dissection of complex traits, a number of genes underlying QTLs associated with plant height that rely on these approaches, have been identified in crop plants, including legumes 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 . Similar major efforts have been made in the past few years towards molecular mapping of low-resolution QTLs governing plant height on multiple intra- as well as inter-specific genetic linkage maps of chickpea 6 29 34 37 55 56 57 58 . However, none of these plant height QTLs could essentially be validated hitherto in diverse genetic backgrounds of chickpea accessions across multiple geographical locations (years).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…For chickpea seed size, many studies have reported QTL by using 100-seed weight (Cobos et al, 2007;Gowda et al, 2011;Karami et al, 2015). While none of these studies reported QTL for seed size using seed volume, all three reported QTL for seed size on LG 4, where the SEV Ca-4 seed volume QTL resides.…”
Section: Traitmentioning
confidence: 99%
“…Using an interspecific cross between Hadas (C. arietinum) with Cr 205 (C. reticulatum), Abbo et al (2005) also identified a significant QTL on the same LG4. Major QTLs for seed size on LG 4 were also identified using different intra-and interspecific crosses Radhika et al 2007;Hossain et al 2010b;Jamalabadi et al 2013;Karami et al 2015). Additionally, minor QTLs on LG1 (Radhika et al 2007;Hossain et al 2010b), LG2 , and LG 8 were also reported (see Chap.…”
Section: Seed Shape and Sizementioning
confidence: 90%